Understanding motivational processes in university rugby players: a preliminary test of the hierarchical model of intrinsic and extrinsic motivation at the contextual level - Paige Pope, J.; Wilson, P. M. (International Journal of Sports Science and Coaching, 2012)
The purpose of this study was to examine the relationship between perceptions of autonomy support, structure and involvement provided by the head coach and motivational processes at mid- and late-season in competitive rugby players. Participants (Mage = 20.17 years, SD = 1.61 years, Range = 18 to 27 years) completed assessments of perceived coaching style and psychological need fulfillment at the mid-season point (nmid-season = 102; 47.05% female) and motivation to continue playing rugby and perceived effort spent playing rugby at the late-season assessment (Nlate-season = 82; 53.64% female). Structural equation modeling analyses provided support for a conceptual model whereby global perceptions of coach support predicted greater need fulfillment which, in turn, was associated with autonomous sport motivation and greater perceived effort. Overall, the results of this study lend partial support for Vallerand's contentions regarding the importance of motivation processes in sport and imply structure and involvement may be important components of a coach's interactional style that impact athletes' motivation.